Apprendendo: um aplicativo para dispositivos móveis de apoio aos processos de ensino e aprendizagem - Menezes Júnior, Jorge Alberto Messa (2016)
The present research, developed in the Professional Master’s Program in Network Educational Technologies (PPGTER) of the Federal University of Santa Maria (UFSM), deals with the development of an application, APPrendendo, which aims to instigate the greater use of the Educational Tablet resource, received by teachers of public high schools through the governmental action called Digital Education – a policy for interactive computers and tablets in their pedagogical practice in classroom. Based on the concept of questions and answers, the application allows teachers to propose challenges to their students in the form of multiple choice questions. In the elaboration of the questions, its functionalities stimulate teachers to use all the resources available in the tablet, such as camera, microphone and Internet access, contributing to their sensitization to the device. The research method used was hypothetico-deductive from the hypothesis of the low use of tablets due to the need of specific applications for the demands of the teachers. By using procedures from action research, the data were obtained through three data collections. Two of them as mixed questionnaires, applied at the beginning and at the end of the research, in which teachers of high schools of Alegrete RS were able to assess their relationship with the Educational Tablet resource before and after the research. Regarding the development of the application, the Web Engineering methodology and the Hybrid Development approach were used. Furthermore, through workshops attended by teachers, the third instrument of data collection, we observed, collected and recorded the requirements for the construction of the research product, APPrendendo application. Through the analysis and comparison of the data collected during the research, we found that the teachers considered the application as a methodological resource capable of being used as a potential tool to promote the use of Educational Tablets. Thus, we concluded that the creation of a specific application for Educational Tablets can contribute to its greater use in classroom by teachers, provided that the application developed is useful and consonant with the reality of teaching, that which during its entire development process the participation of future users is encouraged, and also that the tool exploits all the available resources offering new possibilities for teaching practice.